Mannose-binding lectin has a direct deleterious effect on ischemic brain microvascular endothelial cells. Issue 8 (August 2020) - Neglia, Laura; Fumagalli, Stefano; Orsini, Franca; Zanetti, Adriana; Perego, Carlo; De Simoni, Maria-Grazia
Mannose-binding lectin (MBL), an initiator of the lectin pathway, is detrimental in ischemic stroke. MBL deposition on the ischemic endothelium indicates the beginning of its actions, but downstream mechanisms are not clear yet. We investigated MBL interactions with the ischemic endothelium by exposing human brain microvascular endothelial cells (hBMECs) to protocols of ischemia. Cells were exposed to hypoxia or oxygen–glucose deprivation (OGD), and re-oxygenated with human serum (HS) or recombinant MBL (rhMBL). Hypoxic hBMECs re-oxygenated with HS showed increased complement system activation (C3c deposition, +59%) and MBL deposition (+93%) than normoxic cells. Super-resolution microscopy showed MBL internalization in hypoxic cells and altered cytoskeletal organization, indicating a potential MBL action on the endothelial structure. To isolate MBL effect, hBMECs were re-oxygenated with rhMBL after hypoxia/OGD. In both conditions, MBL reduced viability (hypoxia: −25%, OGD: −34%) compared to conditions without MBL, showing a direct toxic effect. Ischemic cells also showed greater MBL deposition (hypoxia: +143%, OGD: +126%) than normoxic cells. These results were confirmed with primary hBMECs exposed to OGD (increased MBL-induced cell death: +226%, and MBL deposition: +104%). The present findings demonstrate that MBL can exert a direct deleterious effect on ischemic brain endothelial cells in vitro, independently from complement activation.